Study and Comparative Analysis of Existing Recommender Systems - Sanjay; Kumar, Yogesh; Rishi, Rahul (International Journal of Computer Sciences and Engineering, 2019)
This article provides an overview of the various recommender systems, their classifications and comparative study. A recommender system is a software tool used for making suggestions about the items which are of interest to the user and the word “item” refers to the products or services that the system recommends to the individuals. With the emergence of internet, the amount of information available to the users is immense which may lead to confusion while making the final decision of selecting an item. Therefore, it becomes highly imperative to assist the users in selecting the final item. The recommender system attempts to solve the problem by exploring large amount of information and bring personalized content for the users. Such systems are being used for making decisions in different contexts ranging from movies recommendation to news feed.